Integrated Nutrient Management: An Overview of Principles, Problems and Possibilities - Finck, Arnold (Annals of Arid Zone, 2016)
The common concept of fertilization should be widened into the more comprehensive concept of nutrient management being integrated with other production factors. On the basis of nutrient flows and cycles, and in order to reach the yield potential under the prevailing growth conditions, this includes better use of the different nutrient sources, the adaptation of crop rotations to nutrient supply, the consideration of soil heterogeneity and optimum nutrition of crops for better product quality and resistance, finally also prevention of avoidable nutrient losses. Different farming systems require different nutrient management provisions. Exploiting cropping is still widely used, but should pe replaced by sustainable agriculture at low, medium or high yield level (depending on general growth conditions). The regional nutrient transfer (natural or by trade, e.g., into cities) and the global nutrient export pose special nutrient managementÂ· problems. Due to future shortages of some nutrients there will be conflicting objectives, and it will probably be necessary to adapt food demands (via population number) to the resources available, not only for some countries but on a global scale.